1996
DOI: 10.1080/08927029608024100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Studies of Zeolite-A. IV. Structure and Dynamics of NH4+ions in a Rigid Dehydrated Zeolite-A

Abstract: In recent papers C1-31 we reported molecular dynamics simulation studies of ions and water molecules adsorbed in a rigid zeolite-A framework using a simple Lennard-Jones potential plus Coulomb potential with Ewald summation to investigate the structure and dynamics of the adsorbates. In the present paper the same technique is applied to study the local structure and dynamics of NH: ions in a rigid dehydrated zeolite-A. During the preliminary equilibration, the unstable NH,(4) type ion (the 12th ion) is pushed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The most interesting feature is a CH 3 NH 3 + ion at an opposite-4-ring site with no facing CH 3 NH 3 + ions through a 6-ring window. On the other hand, in the MD simulation of NH 4 + -exchanged zeolite-A, the results have shown that there are two facing NH 4 + ions through a 6-ring window with the disappearance of NH 4 + ion at an opposite-4-ring sites against an X-ray diffraction experimental result …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The most interesting feature is a CH 3 NH 3 + ion at an opposite-4-ring site with no facing CH 3 NH 3 + ions through a 6-ring window. On the other hand, in the MD simulation of NH 4 + -exchanged zeolite-A, the results have shown that there are two facing NH 4 + ions through a 6-ring window with the disappearance of NH 4 + ion at an opposite-4-ring sites against an X-ray diffraction experimental result …”
Section: Discussionmentioning
confidence: 95%
“…The four kinds of time correlation functions for CH 3 NH 3 + show the dynamics of the ions which reflect the different structural arrangements of the ions well. The hydrogen bond time correlation functions of four types of CH 3 NH 3 + ions decay more rapidly than those of NH 4 + ions . From the analysis of the characteristic decay times for the H-bonds, about 0.8, 2.9, 0.6, 2.9, 1.6, 0.9, 1.7, and 2.0 hydrogen bonds formed between I and O(2), I and O(3), II and O(2), II and O(3), III and O(1), III and O(2), IV and O(1), and IV and O(3), are retained for 0.83, 1.89, 0.63, 1.61, 0.42, 0.31, 1.11, and 1.26 ps, respectively, before a breaking of the hydrogen bond occurs, leading to a significant exchange of O atoms hydrogen bonded to the ion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations